Can You Handle the Pressure? The Effect of Performance Pressure on Stress Appraisals, Self-regulation, and Behavior - Mitchell, Marie S.; Greenbaum, Rebecca L.; Vogel, Ryan M.; Mawritz, Mary B.; Keating, David J. (Academy of Management Journal, 2019)
Performance pressure focuses employee efforts toward enhanced performance. It is unclear, however, whether performance pressure serves as a productive or unproductive strategy for producing beneficial work behavior. Our research provides clarity on the dynamic nature of performance pressure. We theorize that reactions to performance pressure are influenced by daily fluctuations in how the pressure is appraised, and these fluctuations explain why performance pressure can be a double-edged sword, producing bright and dark side effects for organizations. We predict that, on a daily basis, performance pressure may be appraised as a threat, which promotes self-regulation depletion that explains dysfunctional behavior (i.e., incivility); daily performance pressure may also be appraised as a challenge, which elicits engagement that explains enhanced task proficiency and citizenship. Trait resilience is predicted to moderate these effects, promoting performance pressure to be appraised as a challenge rather than a threat, which then mitigates the depleting effects that produce dysfunctional behavior and enhances the engaging effects that produce functional behavior. Results from an experience sampling study support our predictions. Implications for theory and research are provided.